The Performance Comparison of Socioeconomic and Behavioural Factors as Predictors of Higher Blood Lead Levels of 0-6-Year-Old Chinese Children between 2004 and 2014 - Yixuan Xie; Yaohua Dai; Tao Li (MDPI AG, 2022)
Childhood lead exposure is a commonly known risk factor affecting children's health, and 10 governments have taken actions to reduce children's lead exposure sources. Because lab testing for children's blood lead levels (BLLs) was not popularized easily, socioeconomic and behavioural factors have been usually used as predictors of screening methods. Along with the overall decreasing trend of children's BLLs, the lead-exposure-potential-predicting ability of such factors might be limited or changed over time. Our study aims to compare the predicting ability of multiple factors, including the living environment, economic disparity and personal behaviour differences between 2004 and 2014. With potential predicting factors identified, it could provide direction in identifying individual children facing high-risk lead exposure in the unit of clinics or communities of China. The study was first conducted in 12 cities in China in 2004 and then repeated in 2014 in the same 12 cities with the same method. In total, 27,972 children aged under 7 years were included in this study. With confounding factors adjusted, the child's age, the family's socioeconomic status and the child's personal hygiene habit, especially biting toys, continued to be important predictors of higher blood lead levels among Chinese children. The sex of the child was no longer a predictor. Factors such as the father's occupational contact with lead, residence near the main road and taking traditional Chinese medicine had the potential to be new predictors.